Corporate social responsibility and joint venture governance—the forgotten issues. (1st August 2021) - Fowler, Reg
Abstract: Corporate social responsibility is moving from a 'soft law' phase when international companies are expected to develop and follow voluntary codes of good practice on issues such as human rights, modern slavery, environmental protection and climate change, and into a phase of 'hard law' and enforceable duties of care. This article looks ahead to the issues that such new laws will create for unincorporated joint ventures in the oil and gas sector. The legislation will intentionally get around the principle of corporate separateness with the result that every joint venture participant, the operator and their respective parent companies will have a greater or lesser duty of care to check for and eliminate the same abuses. Will the legislation allow the joint venture participants to rely upon the operator to fulfil those duties for them and how will liability cascade if the duty of care is breached? And what of the state's liability if it also had an obligation not to cause, or to eliminate, the abuses which the joint venture failed to spot and/or remediate? Can the joint venture seek a contribution from the state? These Guiding Principles are grounded in recognition of: (a) States' existing obligations to respect, protect and fulfil human rights and fundamental freedoms; (b) The role of business enterprises as specialized organs of society performing specialized functions, required to comply with all applicable laws and to respect human rights; (c) The need for rights and obligations to be matched to appropriate and effective remedies when breached. 'Guiding Principles on Business and Human Rights—Implementing the United Nations "Protect, Respect and Remedy" Framework'